Myoclonus-Dystonia in an Individual with a Mutation in the GRIN2A Gene - Al Qahtani, Xena; Multhaupt-Buell, Trisha; Sharma, Nutan; Dy-Hollins, Marisela E. (Journal of Pediatric Neurology, 2022)
Mutations in the GRIN2A gene are associated with epilepsy-aphasia spectrum disorders and developmental and epileptic encephalopathies. Associations have been linked with disorders, including autism spectrum disorder and Parkinson's disease. Recently, GRIN2A variants have been reported as a cause of movement disorders in individuals without epilepsy, suggesting that movement disorders should be highlighted as a genetic phenotype associated with pathogenic variants in GRIN2A. We present a case of a male with myoclonus dystonia and without epilepsy found on whole-exome sequencing to have a c.1880G > A; p.S627N variant in the GRIN2A gene. Our case contributes to the expanding phenotypic spectrum of GRIN2A-related disorders and highlights another genetic cause of the myoclonus-dystonia phenotype. GRIN2A should be considered a part of the differential diagnosis of myoclonus-dystonia in individuals with developmental delay without epilepsy.
Keywords: GRIN2A; pediatric movement disorders; hyperkinetic; myoclonus; dystonia